Liquid Crystalline Order and Electric Switching of Upconversion Luminescence in Colloidal Nanorod Suspensions. Issue 9 (18th February 2019) - Park, Sungoh; Mundoor, Haridas; Fleury, Blaise; Davidson, Patrick; van de Lagemaat, Jao; Smalyukh, Ivan I.
Abstract: The polarization‐dependent photon upconversion luminescence properties of large‐scale orientationally ordered soft matter systems formed by colloidal nanorods dispersed in an isotropic solvent are studied. The electrostatically charged photon‐upconverting nanorods form an isotropic dispersion at low concentrations, whereas orientational order and a nematic phase emerge at high concentrations. When an alternating electric field is applied, particles align in the direction of the electric field in both nematic and isotropic phases, though the nature of this electric switching is different in these two phases. Owing to the long‐range orientational order in the nematic phase, the upconversion luminescence from the particles is polarized without an external field. Polarization dependence of these properties can also be electrically induced in an isotropic phase of the colloidal nanorods. Further, the dynamics of switching of photon upconversion luminescence in both nematic and isotropic dispersions are explored and their potential technological uses are dicussed. Abstract : Optical properties of large‐scale orientationally ordered colloidal upconversion nanorods dispersed in an isotropic solvent are studied. The particles dispersed in low concentrations form an isotropic dispersion and orientational order emerges at higher concentrations. The dynamics of upconversion luminescence switching with the applied electric field in both nematic and isotropic dispersions as well as their potential technological uses are discussed.